Conference Theoretical Information Studies Berkeley 2019 - Mark Burgin (Proceedings, 2020)
This paper has a two-fold goal. In the first part, the area of theoretical information studies is described. In second part, contributions to the conference “Theoretical Information Studies” (Berkeley 2019) are characterized.